PERAN PEREMPUAN DALAM SISTEM PERKAWINAN MASYARAKAT ACEH - Alwi Alwi (Indonesian Journal of Dialectics, 2012)
Marriage is  not exclusively a business of the individuals who are going to get married; instead it also involves friends, families, and community as well. Marriage is sacred. That is why it involves many people in performing its procession, particularly for women who have essential roles in it; from the setting of marriage and marriage ceremonies up to its completeness. Whereas men only follow what women said or designed to facilitate a marriage procession.            This research was  aimed: (1) to obtain a description on the participation of community in the Acehnese marriage system, (2) to obtain a description on the motivation of community to participate in the Acehnese marriage system, 3) to obtain data on the forms of community participation in keeping marriage system in the  Acehnese community.This research was conducted by using a descriptive-qualitative method focused on the case of marriage of Acehnese people in the district of Aceh Besar.  Data collection was conducted by using in-depth interview, observation, and documentary study. The researcher also used FGD (Focus Group Discussion) to ensure the accuracy of the analysis.            Marriage sistem in Aceh Besar community has become a social institution to be complied by all community members. Women have a dominant role in every step of marriage ceremony, and together with other people always share their participation in various kinds, such as power, thought, time, or even materials to support the party. The participation was motivated by habitual solidarity, sense of responsibility, care of life, togetherness encouraged by social economic, and job description. Aceh Besar community defend the marriage sistem by obeying customary rules and transformation of marriage ceremonies from old generation to young generation in order to always appreciate their culture as has been showed by Majelis Adat Aceh (MAA) that played an important role in maintaining the preservation of the Acehnese culture.